Young Chinese Consumer’s View on Privacy within the Commercial Context - Liu, Jingwen (2011)
Consume privacy is an important issue for marketers because members of different consumer segments may perform different privacy concerns within a specific context. This paper aims to contribute the understanding of privacy concerns within the commercial context through examining young Chinese consumers’ attitudes to several elements of privacy concerns. In addition, based on the perception of 119 respondents from China aged between 18 to 25 years old, their views on the purpose of data collection through the Internet and the relationship between privacy-related factors and online consumer behaviour are also investigated. Results from the email questionnaire indicate that young consumers in China have a high level of privacy concern, mainly aroused by unauthorized secondary use, followed by information control and collection dimensions. Besides, it is argued that two demographic characteristics (including education and employment status) will affect the level of privacy concern in these three dimensions. Second, the type of personal information requested brings about different degree of individual privacy concerns. Generally, the respondents are more willing to share their demographic information and lifestyle interests with firms instead of their financial data or some information about personal identification. Finally, the results also imply that expertise in Internet and trust in Web merchants play important roles on explaining online purchase-related behaviour.